Mother Figure in Children's Education - Nurhasanah, Nurhasanah; Putra, San (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
This research is based on mothers who participate in earning a living or career women, mothers who feel that formal education at school is more than enough, and mothers who do not understand the importance of the home as the main madrasah. This research uses library research with qualitative research. The steps taken in this research are theme/topic selection, information exploration, determining the focus of research, collecting data sources. Data sources are obtained from relevant literature such as books, scientific articles related to the theme. Data collection techniques by looking for data about things in the form of books, articles, and so on. The research instruments used included a checklist of classification of research materials based on the focus of the study, a writing map, and a research note format. The data analysis technique used by researchers is the content analysis method. The results of this study conclude that the role of mothers in educating children includes paying attention to breastfeeding patterns, parenting patterns, and the role of mothers in shaping children's character can be done through stages of coaching and guidance. Premarital coaching and guidance, prenatal coaching and guidance, and postnatal coaching and guidance.